NON-LITERARY EDUCATION IN HAUSALAND: AN ATTEMPT TOWARDS COMPREHENDING A CONCEPT OF A SOCIETY’S SYSTEM OF EDUCATION FOR LIFE - Saulawa, A. M. (Sokoto Educational Review, 2020)
The aim of this article is to help us to build a conceptual framework for analysis in educational system of the Hausa people, as well as raise specific and general issues of socio-historical significance. Considering such aim, the article also hopes to further contribute information on the processes or patterns in which Non-Literary education was and is still being disseminated for practical use by the Hausa society, hitherto, not a fully explored area.